Metabolite profiling of Boesenbergia rotunda tissue culture callus related to embryogenesis and plant regeneration / Theresa Ng Lee Mei - Theresa Ng, Lee Mei (2017)
Boesenbergia rotunda or fingerroot ginger is commonly found in South East Asia and traditionally used to treat common illnesses. Interest in the medicinal properties of B. rotunda has led to the tissue culture studies of this plant. The exploitation of culture conditions can be expected to affect production of different calli types and cell metabolites. Hence, analysis of primary and secondary metabolites as well as hormones was performed by Ultra Performance Liquid Chromatography Mass Spectrometry to determine the biochemical changes related to embryogenesis and plant regeneration. This was complemented by histological characterization study by microscopy. Primary metabolite profiles showed higher levels of glutamine, arginine and lysine in B. rotunda embryogenic callus compared to non-embryogenic tissues (suspension cells, dry and watery calli). The metabolite markers for embryogenic competency were confirmed in sieved embryogenic cells. Rhizome had the highest flavonoid levels while shoot tips the lowest indicating that flavonoids in shoot tips may result from diffusion from the rhizome. The low endogenous auxin level in embryogenic callus suggests active auxin metabolism to stimulate cell division and elongation for embryogenesis. Histo-morphological study indicated that embryogenic callus can be characterized by the presence of starch granules, fibrils on cell surfaces and bright fluorescent spots after diphenylboric acid 2-aminoethylester staining. Cells in watery callus were non-proliferative, lacking fluorescent spots, nuclei and starch granules, however had apparently higher flavonoid levels, possibly due to higher stain specificity towards selected flavonoids in B. rotunda. Ultimately, the identification of primary metabolite and cell morphology markers in B.rotunda cell cultures together with ongoing genomic studies can improve understanding of molecular processes related to embryogenesis and plant regeneration.